pirABvp-Bearing Vibrio parahaemolyticus and Vibrio campbellii Pathogens Isolated from the Same AHPND-Affected Pond Possess Highly Similar Pathogenic Plasmids - Dong, Xuan; Bi, Dexi; Wang, Hailiang; Zou, Peizhuo; Xie, Guosi; Wan, Xiaoyuan; Yang, Qian; Zhu, Yanping; Chen, Mengmeng; Guo, Chengcheng; Liu, Zhen; Wang, Wenchao; et al. (Frontiers in Microbiology, 2017)
Acute hepatopancreatic necrosis disease (AHPND) is a severe shrimp disease originally shown to be caused by virulent strains of Vibrio parahaemolyticus (VPAHPND). Rare cases of AHPND caused by Vibrio species other than V. parahaemolyticus were reported. We compared an AHPND-causing V. campbellii (VCAHPND) and a VPAHPND isolate from the same AHPND-affected pond. Both strains are positive for the virulence genes pirABvp. Immersion challenge test with Litopenaeus vannamei indicated the two strains possessed similar pathogenicity. Complete genome comparison showed that the pirABvp-bearing plasmids in the two strains were highly homologous, and they both shared high homologies with plasmid pVA1, the reported pirABvp-bearing plasmid. Conjugation and DNA-uptake genes were found on the pVA1-type plasmids and the host chromosomes, respectively, which may facilitate the dissemination of pirABvp. Novel variations likely driven by ISVal1 in the genetic contexts of the pirABvp genes were found in the two strains. Moreover, the VCAHPND isolate additionally contains multiple antibiotic resistance genes, which may bring difficulties to control its future outbreak. The dissemination of the pirABvp in non-parahaemolyticus Vibrio also rises the concern of missing detection in industrial settings since the isolation method currently used mainly targeting V. parahaemolyticus. This study provides timely information for better understanding of the causes of AHPND and molecular epidemiology of pirABvp and also appeals for precautions to encounter the dissemination of the hazardous genes.